2019
DOI: 10.1089/jop.2018.0090
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Medical Record Review to Describe Use of Repository Corticotropin Injection Among Patients with Uveitis in the United States

Abstract: Introduction: Repository corticotropin injection (RCI) has immune-modulatory and anti-inflammatory effects and is approved for multiple indications, including severe and acute chronic allergic and inflammatory processes involving the eye and adnexa. This study describes patient characteristics, treatment patterns, and physicians' assessments of patients with uveitis treated with RCI. Methods: This was a retrospective medical record review of US patients. Eligible patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…Sharma et al (17) found that uveitis is associated with systemic diseases. Nelson et al (18) reported that a specific etiological diagnosis was made in around 61% of patients, and in this study, the etiology was identified or combined with systemic diseases in 60.1% of the patients. It has been reported in the literature that rheumatic diseases predispose patients to the development of uveitis and damage to ocular tissues, and other diseases, such as Behcet's disease, syphilis, serosanguinous spondyloarthritis and psoriatic diseases, can also lead to inflammatory responses in the uvea (19).…”
Section: Discussionsupporting
confidence: 48%
“…Sharma et al (17) found that uveitis is associated with systemic diseases. Nelson et al (18) reported that a specific etiological diagnosis was made in around 61% of patients, and in this study, the etiology was identified or combined with systemic diseases in 60.1% of the patients. It has been reported in the literature that rheumatic diseases predispose patients to the development of uveitis and damage to ocular tissues, and other diseases, such as Behcet's disease, syphilis, serosanguinous spondyloarthritis and psoriatic diseases, can also lead to inflammatory responses in the uvea (19).…”
Section: Discussionsupporting
confidence: 48%
“…The treatment patterns identified in our study may provide insights to improve patient care and help better understand practices for RCI use in RA. Similar real-world effectiveness studies have reported positive clinical outcomes after initiating RCI treatment in patients with refractory diseases, including multiple sclerosis, 40 , 47 sarcoidosis, 12 uveitis, 41 nephrotic syndrome, 48 systemic lupus erythematosus, and dermatomyositis or polymyositis. 20 Outcomes of these studies align with those presented here for RA.…”
Section: Discussionsupporting
confidence: 56%
“…Treatment patterns, medical history and GC dosing are important topics that should be continually discussed by practitioners with patients. 12 , 20 , 40 , 41 Recent ACR guidelines strongly discourage long-term GC use to maintain treatment targets in patients with RA. The European League Against Rheumatism (EULAR) advises GC tapering “as rapidly as clinically possible.” 32 RCI treatment is associated with reduction of the use of concomitant medications such as GCs and DMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, by tailoring the therapy to specific melanocortin receptors different aspects of an immune response can be targeted for regulation (116). The experimental therapeutic use of a-MSH in EAU demonstrates that it is possible to use the mechanisms of ocular immune privilege, and potentially other RPE generated molecules, to suppress inflammation and reestablish ocular immune privilege and tolerance (117,118).…”
Section: Recovery Of Rpe Mediated Immune Regulationmentioning
confidence: 99%